Effect of Inorganic Matter on the Reactivity of Indian Coals - Saha, Sujan; Sharma, B.K.; Chavan, Prakash; Datta, S.; Sahu, G.; Mall, B.K.; Sharma, T. (Asian Journal of Chemistry, 2011)
Coal contains mineral matter as impurities. In the conversion processes, the presence of minerals is inevitably deleterious. But it is also well known that mineral matter in coal affects the reactivity by catalyzing carbon-gas reactions. In the present paper, influence of total mineral matter and major inorganic elements like Si, Al, Fe, Ca, Mg, K and Na on the reactivity of coal samples from different coal fields of India has been investigated. Major elements in the coal samples were analyzed by X-Ray fluorescence (XRF) spectrometer and non-isothermal thermogravimetric analysis was used to determine the reactivity of the coal samples. It has been observed that the reactivity of Indian coals first increases with the increasing mineral matter content, passes through maximum and then decreases. Same trends have been found in the case of alkaline earth metals. Unlike alkaline earth metals, reactivity of coal does not increase with the increasing concentration of alkali metals. This happens due to the variation in available surface area of coal samples with the total mineral matter and inorganic elements. It is also reported in this paper that the slagging and fouling rating for these Indian coal samples are low.